BIOMARKERS IN MEDICINE - PINAR, ATUKEREN; HAFIZE, UZUN. ([S.l.] : BENTHAM SCIENCE PUBLISHER, 2022)
Biomarkers in Medicine is a comprehensive guide to understanding the current and future status of biomarkers. The book features 27 chapters focusing on disease biomarkers for diseases such as cancer, neurodegenerative diseases, cardiac diseases, metabolic conditions and much more. This book supplies readers with the unique insight of experts in multiple specialties in medicine and life sciences who have extensive experience in diagnostics and clinical laboratories. The book includes case studies and practical examples from different classes of biomarkers on different platforms, including new data for biomarkers in different therapeutic indications. In addition to presenting biomarker information, each chapter covers the relevant pathology and also emphasizes on preclinical and clinical manifestation of the disease process. Clinicians managing patients or clinical trials, clinical researchers, clinical laboratories, diagnostic companies, regulatory agencies, medical school graduate students, academic students, and the general public involved in healthcare delivery will all benefit from information presented in this book.
Other MicroRNAs and MicroRNA-Based Classifiers -- Immunophenotypic Biomarkers -- CD30 -- Bcl-6, Bcl-2, and Myc -- Cyclin D1 and SOX-11 -- TP53 and MDM2 -- Immunophenotypic Biomarkers -- Immunohistochemical Biomarkers of Peripheral T-Cell Lymphoma -- Microenvironment-related Biomarkers for Prognosis and Immunotherapy -- BIOMARKERS IN MULTIPLE MYELOMA -- STAGING SYSTEMS -- GENOMIC BIOMARKERS -- Gene Expression Profiling -- NOVEL BIOMARKERS -- Minimal Residual Disease -- Next-Generation Biomarkers in MM -- Immunotherapy-related Biomarkers -- CONCLUSION -- CONSENT FOR PUBLICATION -- CONFLICT OF INTEREST -- ACKNOWLEDGEMENT -- REFERENCES -- Applications of Biomarkers in Cancer Surgery -- Berrin Papila Kundaktepe1,* -- INTRODUCTION -- CIRCULATING TUMOR MARKERS: CLINICAL APPLICATIONS -- Applications Of Tumor Markers In Colorectal Cancer -- Applications of Tumor Markers in Hepatocellular Carcinoma (HCC) -- Applications of Tumor Markers in Pancreatic Adenocarcinoma -- Applications of Tumor Markers In Breast Cancer -- Circulating Tumor Cells -- ENDOCRINE TUMOR MARKERS -- Immunohistochemical and Circulating Tumor Markers of NETs -- CONCLUSION -- CONSENT FOR PUBLICATION -- CONFLICT OF INTEREST -- ACKNOWLEDGEMENT -- REFERENCES -- A Pathophysiological Approach To Current Biomarkers -- Aykut Oruc1,* and Gonul Simsek1 -- CARDIAC BIOMARKERS -- Cardiac Troponins -- Troponin Subunits -- Regulatory Function of Troponin -- Cardiac Troponins as a Biomarker for Acute Myocardial Infarction: The Pathophysiology -- Cardiac Troponins as a Biomarker in Congestive Heart Failure -- Heart-Type Fatty Acid Binding Protein -- Heart-Type Fatty Acid Binding Protein in Acute Myocardial Ischemia -- Glycogen Phosphorylase Isoenzyme BB -- Myocardial Oxygen Deficiency and GPBB Release: The Pathophysiology -- Glutathione S-Transferase P1 -- N-Terminal pro-Brain Natriuretic Peptide.
eBooks on EBSCOhost
Keywords: Biomedical engineering; Radiology; Biochemical markers; Tumor markers; Biomarkers; Biomarkers, Tumor; Radiology; Génie biomédical.; Radiologie; Marqueurs biologiques; Marqueurs tumoraux; biomedical engineering; radiology; MEDICAL / Biochemistry; Biochemical Markers; Clinical Biochemistry; Science; Medical